Epigenome-wide study of brain DNA methylation following acute opioid intoxication. (1st April 2021) - Shu, Chang; Sosnowski, David W.; Tao, Ran; Deep-Soboslay, Amy; Kleinman, Joel E.; Hyde, Thomas M.; Jaffe, Andrew E.; Sabunciyan, Sarven; Maher, Brion S.
Highlights: Epigenome-wide analysis of DNA methylation in human dorsolateral prefrontal cortex. Opioid overdose is marginally associated with methylation within the Netrin-1 gene. Opioid overdose is associated with accelerated phenotypic age. Abstract: Background: Opioid abuse poses significant risk to individuals in the United States and epigenetic changes are a leading potential biomarker of opioid abuse. Current evidence, however, is mostly limited to candidate gene analysis in whole blood. To clarify the association between opioid abuse and DNA methylation, we conducted an epigenome-wide analysis of DNA methylation in brain samples of individuals who died from acute opioid intoxication and group-matched controls. Methods: Tissue samples were extracted from the dorsolateral prefrontal cortex of 153 deceased individuals ( Mage = 35.42; 62 % male; 77 % European ancestry). The study included 72 opioid samples, 53 psychiatric controls, and 28 normal controls. The epigenome-wide analysis was implemented using the Illumina MethylationEPIC BeadChip; analyses adjusted for sociodemographic characteristics, negative control principal components, ancestry principal components, cellular composition, and surrogate variables. Horvath's epigenetic age and Levine's PhenoAge were calculated, and gene set enrichment analyses were performed. Results: Although no CpG sites survived false-discovery rate correction for multiple testing, 13 sites surpassed a relaxed significance threshold (p < 1.0 × 10 −5 ). One of these sites was located within Netrin-1, a gene implicated in kappa opioid receptor activity. There was an association between opioid use and accelerated PhenoAge ( b = 2.24, se = 1.11, p = .045). Gene set enrichment analyses revealed enrichment of differential methylation in GO and KEGG pathways broadly related to substance use. Conclusions: Netrin-1 may be associated with opioid overdose, and future research with larger samples across stages of opioid use will elucidate the complex genomics of opioid abuse.